A new abietane diterpenoid from the roots of Tripterygium regelii. Issue 20 (18th October 2018) - Jiang, Zhi-Hua; Liu, Yan-Ping; He, Miao; Zhao, Jin-Hua; Wang, Ting-Ting; Feng, Xing-Yang; Yue, Hao; An, Ren-Bo; Fu, Yan-Hui
Abstract: A new abietane diterpenoid, tripterregeline A (1 ), together with six known diterpenoids (2 –7 ), were isolated from the roots of Tripterygium regelii . The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparison with data reported in the literature. All isolated compounds were evaluated for their cytotoxicities against five human cancer cell lines: HL-60, SMMC-7721, A-549, MCF-7 and SW480 in vitro . Compounds1 –7 showed significant inhibitory effects against various human cancer cell lines with IC50 values ranging from 0.58 to 21.06 μM. Abstract :